Pre-Service Teacher' Perceptions of Generative AI: Dependency, Effect, and Ethics - Putri, Kristanti Yuntoro; Naf'ihima, Fika Ar-Rizqi (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2025)
This study investigates pre-service teachers’ dependency on Generative Artificial Intelligence (GenAI), their perceptions of its effects, and their awareness of academic ethics. Employing a descriptive quantitative research design, data were collected through an online questionnaire adapted from Chan & Hu (2023) and the Indonesian Ministry of Education’s Guidebook on GenAI Usage (2024). The study involved 100 pre-service teachers from the English Education Study Program, with 46 valid responses. The results indicate that while most participants are uncertain about their dependency on GenAI, many acknowledge its benefits in saving time, providing unique insights, and offering personalized feedback. However, concerns remain regarding its impact on digital competence, social interaction, teamwork, critical thinking, and leadership skills. Additionally, perceptions of GenAI’s effect on problem-solving skills are evenly divided. In terms of academic ethics, more than half of the respondents are unsure whether using GenAI undermines ethical values. Nonetheless, most pre-service teachers report that they rewrite AI-generated content in their style and provide references. Given the high level of uncertainty in responses, this study highlights the need for universities and lecturers to provide clearer and more intensive guidance on responsible GenAI usage. Future research should explore its impact on academic skill development and employ alternative research designs for deeper insights.